2018
DOI: 10.1186/s12887-018-1327-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth during the first year in infants affected by neonatal abstinence syndrome

Abstract: BackgroundInfants with neonatal abstinence syndrome (NAS) initially experience neurologic excitability, poor feeding, and/or hyperphagia in the setting of increased metabolic demand. Because the longitudinal effects of these early symptoms and behaviors on weight trends are unknown, we sought to contrast weight gain patterns through age 1 year for infants diagnosed with NAS with matched controls.MethodsRetrospective cohort of 70 singletons with a gestational age of ≥37 weeks and an ICD-9 or ICD-10 diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Similarly, given the relatively small effects of PDMPs on NAS and the overall low incidence of NAS compared to other outcomes, it is not surprising that one finds no evidence of any significant effects of the adoption of operational PDMPs on prematurity and infant mortality. Furthermore, there is evidence suggesting that different opioids may have heterogeneous effects on weight gain (Kandall et al, 1976;Hulse et al, 1997), and recent evidence finds no evidence of significant differences in the weight trends of NAS children compared to appropriately matched counterparts (Corr et al, 2018). At the same time, there is increasing evidence regarding the long-run effects of NAS on child development (Reddy et al, 2017;Fill et al, 2018).…”
Section: Effects On Birth Outcomesmentioning
confidence: 99%
“…Similarly, given the relatively small effects of PDMPs on NAS and the overall low incidence of NAS compared to other outcomes, it is not surprising that one finds no evidence of any significant effects of the adoption of operational PDMPs on prematurity and infant mortality. Furthermore, there is evidence suggesting that different opioids may have heterogeneous effects on weight gain (Kandall et al, 1976;Hulse et al, 1997), and recent evidence finds no evidence of significant differences in the weight trends of NAS children compared to appropriately matched counterparts (Corr et al, 2018). At the same time, there is increasing evidence regarding the long-run effects of NAS on child development (Reddy et al, 2017;Fill et al, 2018).…”
Section: Effects On Birth Outcomesmentioning
confidence: 99%
“…The average weights of infants in the intervention group, who had stronger self-efficacy and commitment to exclusive breast feeding, were higher than those of infants in the control group, who were formula-fed or supplemented. A few more studies have indicated that the weight gain of infants who were exclusively breastfed during the first trimester after birth was higher than those who had nonexclusive nutrition with supplementary food or formula-fed ( 37 ). These results match those observed in an earlier study.…”
Section: Discussionmentioning
confidence: 99%
“…We also wanted the rodent pups to undergo morphine withdrawal and potentially experience characteristics of NOWS that can be investigated before weaning and might produce long-term behavioral consequences. Most clinical and preclinical studies have shown that offspring from opioid-dependent mothers display either reduced body weight or no change in body weight (Corr, Schaefer, & Paul, 2018;Dutriez-Casteloot et al, 1999;Gagin et al, 1997;Jones et al, 2010;Kaltenbach et al, 2018;Klausz et al, 2011;Laborie et al, 2005;Ramsey et al, 1993;Shen et al, 2016;Siddiqui et al, 1997;Siu & Robinson, 2014;Timár et al, 2010). However, some preclinical studies like Chiang et al (2010) and Timar et al (2010) have reported increased body weight in PND 7, PND 14, and PND 21 offspring after maternal morphine exposure.…”
Section: -Discussionmentioning
confidence: 99%